The dark vineyard [large type] - Walker, Martin, 1947 January 23- (Walker, Martin, 1947 January 23- Bruno series., 2010)
It's been only a few weeks since Police Chief Bruno Courreges said goodbye to his lover and partner in justice, and a mystery is precisely what he needs to distract him from heartbreak. When a research station for genetically modified crops is burned down Bruno suspects the fervent environmentalists who live nearby, but the fire is only the first in a string of intrigues centering on the fertile soil of Saint Denis.